Linguistic validation of the 20 item-chronic venous disease quality-of-life questionnaire (CIVIQ-20). (August 2014) - Launois, R; Mansilha, A; Lozano, F
Our objective was to review the linguistic validation of the 20 item-ChronIc Venous dIsease quality-of-life Questionnaire (CIVIQ-20) in the countries that have used it since its publication in 1996. Seventeen linguistic versions of CIVIQ-20 were validated using forward/backward methodology in patients presenting with chronic venous disease, stages C0s to C4 of the CEAP (clinical, aetiological, anatomical and pathological) classification (patients with venous ulcers were excluded). Most obstacles in the cross-cultural validation of CIVIQ-20 related to content and semantic equivalence. Confirmation of cultural relevance by experts with the native language as their mother tongue and the use of forward/backward translation methodology partly resolved these difficulties. CIVIQ-20 is valid for the assessment of treatment effects in multinational studies.